Geschichtspolitik als Unternehmenskommunikation : Krupp im 20. Jahrhundert - Roelevink, Eva-Maria 1984- (De Gruyter, 2023)
There is hardly any other German company that was so polarizing in the twentieth century as Krupp. Publicly, "Krupp haters" and "Krupp fans" exchanged high-profile punches. Roelevink delves into this conflict, inquiring into the history policy of the company and showing to what extent and in what way Krupp was actively involved in the public negotiation of its own image